2019
DOI: 10.1038/s41372-019-0347-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of drugs used to constrict the patent ductus arteriosus: a secondary analysis of the PDA-TOLERATE trial (NCT01958320)

Abstract: Objective: To evaluate the effectiveness of drugs used to constrict patent ductus arteriosus (PDA) in newborns <28 weeks. Methods: We performed a secondary analysis of the multi-center PDA-TOLERATE trial ( ). Infants with moderate-to-large PDAs were randomized 1:1 at 8.1±2.1 days to either Drug treatment (n=104) or Conservative management (n=98). Drug treatments were assigned by center rather than within center (acetaminophen: 5 centers, 27 infants; ibuprof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 38 publications
(49 reference statements)
2
56
1
1
Order By: Relevance
“…The authors found that early routine treatment of medium and large PDAs at the end of the first week in infants born during the 28th gestational week does not reduce the presence of PDA ligations or PDAs during discharge, does not improve any of the predetermined secondary results and delays full enteral nutrition. Furthermore, they found that it increases the risk of late-onset sepsis and death in infants ≥ 26 week gestation [30].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that early routine treatment of medium and large PDAs at the end of the first week in infants born during the 28th gestational week does not reduce the presence of PDA ligations or PDAs during discharge, does not improve any of the predetermined secondary results and delays full enteral nutrition. Furthermore, they found that it increases the risk of late-onset sepsis and death in infants ≥ 26 week gestation [30].…”
Section: Discussionmentioning
confidence: 99%
“…2,[4][5][6][7][8][9][10][11][21][22][23][24][25] To address this concern, a recent multicenter RCT compared the efficacy of the 3 drugs in infants delivered exclusively before 28 weeks of gestation who still had a moderate-tolarge PDA at the end of the first week. 26 The trial found that infants treated with indomethacin had the greatest rate of constriction among the 3 drugs tested: when compared with the rate of spontaneous PDA constriction (which was 20%) during the 7-10 days after enrollment, the relative risk of indomethacin-induced closure was 3.21 (95% CI, 2.05-5.01), followed by ibuprofen at 2.03 (95% CI, 1.05-3.91), and acetaminophen at 1.33 (95% CI, 0.55-3.24). 26 It should be noted that, even in the infants studied by Kumar et al, the rate of ductus closure after paracetamol appeared to be less robust than after ibuprofen.…”
mentioning
confidence: 99%
“…26 The trial found that infants treated with indomethacin had the greatest rate of constriction among the 3 drugs tested: when compared with the rate of spontaneous PDA constriction (which was 20%) during the 7-10 days after enrollment, the relative risk of indomethacin-induced closure was 3.21 (95% CI, 2.05-5.01), followed by ibuprofen at 2.03 (95% CI, 1.05-3.91), and acetaminophen at 1.33 (95% CI, 0.55-3.24). 26 It should be noted that, even in the infants studied by Kumar et al, the rate of ductus closure after paracetamol appeared to be less robust than after ibuprofen. 4 Although the ultimate rate of PDA closure after 1 or 2 courses of paracetamol was similar to the rate of closure after ibuprofen, the rate of PDA reopening was higher after paracetamol and more neonates who were treated initially with paracetamol required a second course of the drug.…”
mentioning
confidence: 99%
See 2 more Smart Citations